Scientific aspects of the formation of the Chinese information strategy in the new media - Fan, Jia (Journal of the Belarusian State University. Journalism, 2019)
The article aims to chronologically analyze the scientific support for the formation of the Chinese communication strategy since the end of the last century, after the emergence of new media in the world, and their impact on the transformation of traditional media. The scientific publications of the leading Chinese scientists of the last 20 years, as well as Chinese dissertation research on this topic are considered. The scientific research traces the phasing, continuity, deepening of the target tasks, approach to the definition of the paradigm of new media in general, their utilitarian influence and significance for Chinese mass media.
Keywords: journalism; new media; traditional media; information strategy of China; scientific research; mass media